ANALYSIS OF STATIC AND KINETIC FRICTION COEFFICIENTS FOR PAIR SURFACE MATERIAL - Hana Mufida, Dhia
This study aims to determine the coefficient of static friction ???????????????? and coefficient of kinetic friction ???????????????? of several types of pair surface material with the parameters that influence it. The main system used in the experiment includes an object with block shaped that slides on an inclined plane with adjustable slope angle of the plane. The study assessed through block motion experiments on inclined plane to determine ???????? by finding the slope angle of the plane when object will start to move. Whereas to determine ???????? by observing the slide of objects from the top of the incline while recorded it in video. Furthermore, it will be analyzed using video tracker to obtain object velocity to time graphs with various angle variations. As the results that static and kinetic friction coefficients were value of paired product from block material and inclined plane. Portable box as learning media had proven mass and surface area of objects didn’t effect static and kinetic friction coefficients material. In addition, some materials with lower Mohs hardness scale, i.e. aluminum < copper < brass < glass < steel had correlation with result of it friction coefficients.